2016
DOI: 10.3748/wjg.v22.i43.9571
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus may affect the long-term survival of hepatitis B virus-related hepatocellular carcinoma patients after liver transplantation

Abstract: AIMTo determine whether diabetes mellitus (DM) affects prognosis/recurrence after liver transplantation (LT) for hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC).METHODSA retrospective study was conducted between January 2000 and August 2013 on 1631 patients with HBV-related HCC who underwent LT with antiviral prophylaxis. Patient data were obtained from the China Liver Transplant Registry (https://www.cltr.org/). To compare the outcomes and tumor recurrence in the HBV-related HCC patients with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…This analysis showed that only diabetes marginally reduces the overall survival of HCC patients. Our result supports and extends to Western HCC patients -managed in an updated way -the findings of quite old studies usually based on small surgical cohorts of Asiatic patients, reporting an adverse impact of diabetes on the outcome of patients with cirrhosis and HCC [36][37][38][39][40]. Nevertheless, despite these evidences and the well know pathogenic role of diabetes on cardiac, renal, and neurologic diseases, other studies report a better prognosis of patients with HCC and diabetes as compared to non-diabetic patients [8,41].…”
Section: Accepted Articlesupporting
confidence: 87%
“…This analysis showed that only diabetes marginally reduces the overall survival of HCC patients. Our result supports and extends to Western HCC patients -managed in an updated way -the findings of quite old studies usually based on small surgical cohorts of Asiatic patients, reporting an adverse impact of diabetes on the outcome of patients with cirrhosis and HCC [36][37][38][39][40]. Nevertheless, despite these evidences and the well know pathogenic role of diabetes on cardiac, renal, and neurologic diseases, other studies report a better prognosis of patients with HCC and diabetes as compared to non-diabetic patients [8,41].…”
Section: Accepted Articlesupporting
confidence: 87%
“…To our knowledge, there are several studies that have compared the impact of DM on survival and tumour recurrence in HCC patients. Zhang et al reported that DM patients had significantly worse overall survival than those without DM, but there was no significant difference in recurrence‐free survival rates between these two groups. However, Connolly et al indicated that though the median survival time for the non‐DM patients was longer than that for the DM patients, no significant differences were observed.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical studies regarding the impact of patient pre‐existing DM on post‐transplant HCC recurrence are still limited, and whether DM adversely affects the prognosis of HCC patients remains controversial in transplant cohort. Some studies have shown that prior DM does not impact recurrence and patient survival; others found worsened overall survival but no increased risk of recurrence . Moreover, all of these studies included limited numbers of patients owing to cases from single centre or with homologous disease background; possible confounding variables could not be taken into account, and none of these studies was performed on an intention‐to‐treat strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result supports and extends to Western HCC patients-managed in an updated way-the findings of quite old studies usually based on small surgical cohorts of Asiatic patients, reporting an adverse impact of diabetes on the outcome of patients with cirrhosis and HCC. [36][37][38][39][40] Nevertheless, despite these evidences and the well-known pathogenic role of diabetes on cardiac, renal and neurological diseases, other studies report a better prognosis of patients with HCC and diabetes as compared to non-diabetic patients. 8,41 This surprising and difficult to understand discrepancy probably relies on the effect of selection biases and confounding factors on results.…”
Section: Discussionmentioning
confidence: 99%